A local maximum likelihood model of crop yield distributions. (30th December 2019) - Wu, Ximing; Zhang, Yu Yvette
Abstract: In this note, we propose a local maximum likelihood estimator for spatially‐dependent distributions. Our estimator adopts the Poisson regression approach for density ratio models and incorporates spatial smoothing via local regression. We also present a method of smoothing parameter selection. We illustrate this easy‐to‐implement estimator with an application to the estimation of corn yield distributions of Iowa counties. The usefulness of the approach is further demonstrated via an application to the estimation of crop insurance premium. Abstrait: Dans cette note, nous proposons un estimateur local du maximum de vraisemblance pour des distributions spatialement dépendantes. Notre estimateur adopte l'approche de régression de Poisson pour les modèles de rapport de densité et intègre le lissage spatial via une régression locale. Nous présentons également une méthode de lissage de la sélection des paramètres. Nous illustrons cet estimateur facile à mettre en œuvre avec une application de l'estimation de distributions de rendement de maïs dans les comtés de l'Iowa. L'utilité de l'approche est également démontrée en l'appliquant à l'estimation de prime d'assurance récolte.